Application of Hybrid Polymer as Laser Devices Based on 2D Grating with Square Structure - Sahrul Hidayat; Fitrilawati Fitrilawati; Ayi Bahtiar; Rustam Eefendi Siregar; Rahmat Hidayat; M Ozaki (Institut Teknologi Bandung, 2010)
Two dimensional gratings have been fabricated by laser interference method on hybrid polymer films doped with 4-dicyanmethylene-2-methyl-6-(p-dimethyl-aminostyryl)-4H-Pyran (DCM). The gel precursor of hybrid polymer was synthesized by sol-gel route using 3-(trimethoxysilyl)-propyl-methacrylate (TMSPMA). The film was exposed by laser interference of Nd-YAG laser yield square lattice of 2D-grating with periodicities 391 nm and 405 nm. The characteristic of lasing was investigated using strip-line excitation light of second harmonic generation (SHG) of Nd-YAG laser (λ = 532 nm). The lasing wavelengths are observed at (588 nm ± 2) and (606 nm ± 2 nm) for grating period of 391 nm and 405 nm, respectively. The spectral width of lasing is about 2 nm at pumping power 6.6 mJ/pulse.cm2.